USING DUOLINGO APPLICATION TO IMPROVE ENGLISH VOCABULARY MASTERY OF THE JUNIOR HIGH SCHOOL STUDENTS - Putri, Al-khaerunissa; Dollah, Syarifuddin; Korompot, Chairil Anwar (JTechLP: Journal of Technology in Language Pedagogy, 2025)
This research aimed to evaluate the effectiveness of the Duolingo application in enhancing English vocabulary mastery among junior high school students and to assess their perceptions of the application after using it. The study adopted a quantitative approach, employing a cluster random sampling method and a pre-experimental design. The participants consisted of 22 students from grade 8B at SMP Negeri 3 Mare in Bone Regency, South Sulawesi. Data were obtained through pretests, posttests, and questionnaires that explored students' opinions about Duolingo. A t-test analysis with a significance level of 0.05 revealed a probability value (sig. 2-tailed) of 0.000, which was lower than the threshold. This led to the rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (H1). The findings concluded that the Duolingo application significantly improves students' vocabulary mastery. Furthermore, students' perceptions of the application were predominantly positive, with most respondents agreeing or strongly agreeing with the statements in the questionnaire.